Review Of The Execution Of The Decision Of The Lubuklinggau State Court Number 15/Pdt.G/2018/Pn Llg - Randa Alala; Slamet Muljono; Emelia Kontesa (Universitas Bengkulu, 2022)
In 2018, there was a lawsuit filed by Asbiati and Murisa Binti Nang Agus as the Plaintiffs against PT. Buana Sriwijaya Sejahtera (PT. BSS) as Defendant I, Plantation Cooperation of Tritunggal Jaya as Defendant II, Regent of Musi Rawas Utara as Defendant III, and Village Head of Biaro Lama as Co-Defendant that was submitted to the Lubuklinggau District Court and had been decided in Decision Number: 15/ Pdt. G/2018/PN.Llg In the course, this decision could not be executed. This study discusses the reasons for the Lubuklinggau District Court Decision Number 15/Pdt.G/2018/PN.Llg which has permanent legal force (inkracht van gewijsde) cannot be executed, as well as discussing the obstacles to the execution of the Lubuklinggau District Court Decision Number 15/Pdt.G/2018/PNLlg. Execution is the implementation of a Court Decision which has permanent legal force (in kracht van gewijsde) which is carried out forcibly by the District Court where the parties file a lawsuit caused by the losing party in the case rejecting to comply with and to carry out the Court's Decision. The approach used in this study was a normative juridical approach. This study used secondary data obtained from primary and secondary legal materials. The results of this study describe a decision that cannot be executed because there is no argument in the Plaintiffs' lawsuit that places a confiscation of collateral (conservatoir beslaag), and confiscation of execution (excekutorial beslaag) for a decision that has permanent legal force (inkracht van gewijsde), so that the decision does not have executive power. While the obstacles that arise are in the form of the absence of a time limit that serves as a guide for the Head of the Lubuklinggau District Court to carry out and determine an execution of a decision, and the resistance by the executed party who does not want to voluntarily carry out the contents of the judge's decision.